ANALYSIS OF FINANCIAL PERFORMANCE MEASUREMENT OF THE SOUTH SULAWESI PROVINCIAL GOVERNMENT BASED ON THE VALUE FOR MONEY PRINCIPLE - Amrie Firmansyah; Galih Satriya Praptama; Tyara Laritza Gistiani (IPSAR (International Public Sector Accounting Review), 2023)
Measuring the public sector performance is an important matter to be implemented to assess the success of local financial management and promote public accountability. This research was conducted to review the Province of South Sulawesi's financial performance, which is the research object for 2017 to 2021. The method applied in this study is a quantitative approach using a mathematical ratio, namely value for money (VFM), or the 3E concept, namely economic, efficiency, and effectiveness. Meanwhile, this research utilizes secondary data from the local government budget (Anggaran Pendapatan dan Belanja Daerah/APBD) data published by the Directorate General of Fiscal Balance, Ministry of Finance. The study results show that the Provincial Government of South Sulawesi's financial performance still needs to be more economical and efficient. However, it has effectively managed its local government budget.